Development of dendrite polarity in Drosophila neurons - Hill, Sarah E (BioMed Central, 2012)
BACKGROUND: Drosophila neurons have dendrites that contain minus-end-out microtubules. This microtubule arrangement is different from that of cultured mammalian neurons, which have mixed polarity microtubules in dendrites. RESULTS: To determine whether Drosophila and mammalian dendrites have a common microtubule organization during development, we analyzed microtubule polarity in Drosophila dendritic arborization neuron dendrites at different stages of outgrowth from the cell body in vivo. As dendrites initially extended, they contained mixed polarity microtubules, like mammalian neurons developing in culture. Over a period of several days this mixed microtubule array gradually matured to a minus-end-out array. To determine whether features characteristic of dendrites were localized before uniform polarity was attained, we analyzed dendritic markers as dendrites developed. In all cases the markers took on their characteristic distribution while dendrites had mixed polarity. An axonal marker was also quite well excluded from dendrites throughout development, although this was perhaps more efficient in mature neurons. To confirm that dendrite character could be acquired in Drosophila while microtubules were mixed, we genetically disrupted uniform dendritic microtubule organization. Dendritic markers also localized correctly in this case. CONCLUSIONS: We conclude that developing Drosophila dendrites initially have mixed microtubule polarity. Over time they mature to uniform microtubule polarity. Dendrite identity is established before the mature microtubule arrangement is attained, during the period of mixed microtubule polarity.